A novel Th1-type T-cell immunity-biasing effect of malate dehydrogenase derived from Mycobacterium avium subspecies paratuberculosis via the activation of dendritic cells. (April 2018) - Kim, Woo Sik; Kim, Jong-Seok; Shin, Min-Kyoung; Shin, Sung Jae
Highlights: MAP MDH activates DCs with increased expression of TNF-α, IL-1β, IL-6, and IL-12p70, but not IL-10. MAP MDH induces DC maturation by activation of NF-κB and MAPK. MAP MDH-treated DCs induce naïve CD4 + /CD8 + T cell proliferation and IFN-γ secretion in CD4 + T cells. MAP MDH promotes Th1 type immunity via DC activation. Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) is the causative pathogen of Johne's disease in ruminants, characterized by chronic granulomatous enteritis; it also has zoonotic potential and is associated with Crohn's disease in humans. A better understanding of the mycobacterial antigens and their roles in the host immune response may facilitate the rational design of control strategies, including the development of effective vaccines and diagnostic tools. However, the functional roles of a large proportion of MAP antigens involved in modulating the host immune response remain unknown. In this study, an immunological role of MAP malate dehydrogenase (MDH, MAP2541c), an antigen that is upregulated in stress culture conditions, such as nutrient starvation and hypoxia, in polarizing naïve CD4 + /CD8 + T cells toward Th1-biased T-cell immunity via the activation of dendritic cells (DCs) was identified. DCs treated with MAP MDH displayed characteristics of the activated and mature immune status, with augmented expression of cell surface molecules and pro-inflammatory cytokines, including TNF-α, IL-1β, IL-6, and IL-12p70, but not IL-10, along with a dose-dependent decrease in the antigen uptake capacity. A mechanistic investigation revealed that the observed DC maturation is mediated by the activation of JNK, ERK, and p38 MAP kinases, and the NF-κB signaling pathway. Notably, DCs activated by MAP MDH treatment promoted naïve CD4 + /CD8 + T cell proliferation; in particular, they effectively polarized naïve CD4 + T cells to secrete IFN-γ and IL-2 and activate T-bet, but, unlike the LPS control, did not influence IL-5 and GATA-3. These results indicated that MAP MDH has the potential to induce the Th1 cell response via DC activation. Collectively, our data demonstrated that MAP MDH is a novel immunostimulatory antigen that drives Th1-biased T cell polarization via interactions with DCs, suggesting that MDP MDH has the potential to be an effective MAP vaccine antigen target and diagnostic marker.